Tumor metabolic regulators: key drivers of metabolic reprogramming and the promising targets in cancer therapy - Kun Huang; Ying Han; Yihong Chen; Hong Shen; Shan Zeng; Changjing Cai (Molecular Cancer)
Abstract Metabolic reprogramming within the tumor microenvironment (TME) is a hallmark of cancer and a crucial determinant of tumor progression. Research indicates that various metabolic regulators form a metabolic network in the TME and interact with immune cells, coordinating the tumor immune response. Metabolic dysregulation creates an immunosuppressive TME, impairing the antitumor immune response. In this review, we discuss how metabolic regulators affect the tumor cell and the crosstalk of TME. We also summarize recent clinical trials involving metabolic regulators and the challenges of metabolism-based tumor therapies in clinical translation. In a word, our review distills key regulatory factors and their mechanisms of action from the complex reprogramming of tumor metabolism, identified as tumor metabolic regulators. These regulators provide a theoretical basis and research direction for the development of new strategies and targets in cancer therapy based on tumor metabolic reprogramming.